Caracterización de daños de lepidópteros en frutos de kiwi en plantaciones del sudeste bonaerense - Alonso, Mariangeles; Divita, Ignacio Federico; Lozano Miglioli, Jorge Raúl; David, Maria Angela; Mondino, Eduardo Ariel; Yommi, Alejandra Karina (Sociedad Uruguaya de Fitopatología, 2024)
Poster